PROGRAM PARENTING DALAM MENGEMBANGKAN PERKEMBANGAN KARAKTER ANAK USIA DINI DI PAUD SAI PREMA KUMARA DENPASAR - Dewi Sukmawati I Dewa Ayu (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Education is a process for changing the behavior of each individual to be able to form good character. Education is obtained in three domains, namely at school, in the family and in the community in the education stage, all of which have their respective differences in educating children. The nation's children are currently experiencing moral degradation, especially for early age children who are now able to take actions that are beyond the boundaries such as bullying and addiction to technology tools. To connect education at school and home, of course, there must be a program that can connect this, one of which is the parenting program. The issues that will be discussed include 1. How is the parenting program implemented by Sai Prema Kumara PAUD to develop character education for Early Childhood? 2. What are the obstacles faced by PAUD Sai Prema Kumara in parenting programs to develop character education in early childhood? 3. What are the implications of parenting programs for developing character education in early childhood? The theories used to analyze the problem are humanistic theory, behaviorism theory, structural-functional theory in parenting. The subjects in this study were teachers, parents, and principals of PAUD Sai Prema Kumara Denpasar. The data collection methods are observation, interview, a document study, and literature study. The technique of determining informants using purposive sampling and data analysis techniques such as data reduction, data classification, data reduction and data verification/conclusion. The results showed (1) the implementation of the parenting program that was implemented by PAUD Sai Prema Kumara to develop early childhood character education. (2) the obstacles faced by PAUD Sai Prema Kumara in parenting programs to develop character education in early childhood. (3) implications of parenting programs to develop character education in early childhood.